2021
DOI: 10.1177/02692155211038728
|View full text |Cite
|
Sign up to set email alerts
|

Joint mobilization and therapeutic exercises in the hands of patients with systemic sclerosis: A preliminary randomized controlled trial

Abstract: Objective: To investigate the effectiveness of Maitland’s joint mobilization and therapeutic exercises on the functionality of the hands in patients with systemic sclerosis. Design: Randomized controlled trial. Setting: Tertiary university hospital. Subjects: Twenty-four patients diagnosed with systemic sclerosis according to ACR/EULAR 2013 criteria; age ⩾18 years and Cochin Hand Functional Scale (COCHIN) score ⩾10. They were randomized to physical therapy group ( n = 12) or control group ( n = 12). Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…• Supervised rehabilitation therapy is essential for the improvement of hand motility and pain (106,107).…”
Section: Take Home Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…• Supervised rehabilitation therapy is essential for the improvement of hand motility and pain (106,107).…”
Section: Take Home Messagesmentioning
confidence: 99%
“…• Growing interest is raising towards non-pharmacological treatments, such as rehabilitation interventions (106,107).…”
Section: Take Home Messagesmentioning
confidence: 99%
“…After thorough reading of the documents, 12 articles were excluded. Finally, a total of 8 RCTs 33–40 involving 487 participants were included – 249 in the experimental group and 238 in the control group (see Table 1). A more detailed description of this process can be found in the PRISMA flow diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies had been conducted in Italy, 33,35,36,40 1 in France, 38 1 in Brazil, 37 1 in the Netherlands 39 and 1 in Turkey 34 . The included studies evaluated different non‐pharmacological interventions for individuals with a diagnosis of SSc.…”
Section: Resultsmentioning
confidence: 99%
“…Existing evidence, however, tends to be descriptive or from very small trials with important limitations in design, conduct, and reporting [ 15 ]. As part of an ongoing living systematic review [ 16 ], we identified 11 randomized controlled trials (RCTs) that evaluated physical or occupational therapy interventions designed specifically to improve hand function in SSc, but none analyzed data from ≥ 30 participants per trial arm [ 13 , 14 , 17 25 ]. Two other small trials have evaluated a 12-week multidisciplinary day treatment program ( N = 53) [ 26 ] and a minimally supervised general home exercise program ( N = 44) [ 11 ]; both included hand exercises and reported that the interventions improved grip strength.…”
Section: Introductionmentioning
confidence: 99%